Application of selective F tests in joint regression analysis - Pereira, D. G. (2012)
Joint Regression Analysis (JRA) has been widely used to compare cultivars. In this technique a linear regression is adjusted per cultivar. The slope of each regression measures the ability of the corresponding cultivar to answer to variations in productivity. Recently, we are mainly interested in cultivars with better response to high fertility. To single out such cultivars, in the context of Joint Regression Analysis, selective F-tests are used to see if there is a cultivar with significantly larger slope.